HADRON SPECTRUM IN QCD AT 6/G2=5.6 - Bitar, K; Edwards, R; Heller, U; Kennedy, A; Liu, W; Degrand, T; Gottlieb, S; Krasnitz, A; Kogut, J; Renken, R; Ogilvie, M; Rossi, P; et al. (1990)
We have carried out a simulation of QCD using the hybrid-molecular-dynamics algorithm with two flavors of staggered quarks. The spectrum was calculated for 6g2=5.6 and dynamical quark masses amq=0.025 and 0.01. Lattice sizes of 124, 123×24, and 164 were used to generate the gauge configurations. Hadron propagators were calculated with both staggered and Wilson quarks on doubled or quadrupled latices. Finite-size effects are visible on the smaller lattices. Some improvement in the to-nucleon mass ratio and chiral symmetry is seen as compared to previous calculations, but, as in most lattice calculations, the proton-to mass ratio remains larger than in the real world and the proton splitting is too small. © 1990 The American Physical Society.